Molecular Characterization of Staphylococcus aureus Plasmids Associated With Strains Isolated From Various Retail Meats - Neyaz, Leena; Rajagopal, Nisha; Wells, Harrington; Fakhr, Mohamed K. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is considered one of the most important foodborne bacterial pathogens causing food poisoning and related illnesses. S. aureus strains harbor plasmids encoding genes for virulence and antimicrobial resistance, but few studies have investigated S. aureus plasmids, especially mega plasmids, in isolates from retail meats. Furthermore, knowledge about the distribution of genes encoding replication (rep) initiation proteins in food isolates is lacking. In this study, the prevalence of plasmids in S. aureus strains isolated from retail meats purchased in Oklahoma was investigated; furthermore, we evaluated associations between rep families, selected virulence and antimicrobial resistance genes, and food source origin. Two hundred and twenty-two S. aureus isolates from chicken (n=55), beef liver (n=43), pork (n=42), chicken liver (n=29), beef (n=24), turkey (n=22), and chicken gizzards (n=7) were subjected to plasmid screening with alkaline lysis and PFGE to detect small-to-medium sized and large plasmids, respectively. The S. aureus isolates contained variable sizes of plasmids, and PFGE was superior to alkaline lysis in detecting large mega plasmids. A total of 26 rep families were identified by PCR, and the most dominant rep families were rep10 and rep7 in 164 isolates (89%), rep21 in 124 isolates (56 %), and rep12 in 99 isolates (45%). Relationships between selected rep genes, antimicrobial resistance and virulence genes, and meat sources were detected. In conclusion, S. aureus strains isolated from retail meats harbor plasmids with various sizes and there is an association between rep genes on these plasmids and the meat source or the antimicrobial resistance of the strains harboring them.